2016
DOI: 10.1002/dc.23479
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing thyroid gland tumors: Infarction as consequence of FNA?

Abstract: Total histopathological blocking with thorough check of capsular areas is recommended in necrotic tumors. Vanishing thyroid lesion phenomenon is rare, but in cases of disappearance of tumor, preoperative cytology diagnosis is the only clue for the patient management. Diagn. Cytopathol. 2016;44:568-573. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It is noteworthy that, in contrast to our data, all the cases of vascular changes were associated with necrosis. Our own necrosis cases were not accompanied by neovascularisation [21] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is noteworthy that, in contrast to our data, all the cases of vascular changes were associated with necrosis. Our own necrosis cases were not accompanied by neovascularisation [21] .…”
Section: Discussionmentioning
confidence: 98%
“…Several subsequent studies confirmed their observations [16][17][18][19] . Thyroid FNAB-related histopathological changes often include haemorrhage, fibrosis, granulation tissue, and necrosis [15][16][17][18][19][20][21] . Necrosis and infarction of the thyroid gland had already been described before the WHAFFT concept, mainly as case reports and case series [22,23] .…”
mentioning
confidence: 99%
“…The size of the FNA needle and the number of needle punctures used may influence the post-FNA changes or US interval changes in STNs. Previous studies have reported that needle injury is known to be closely associated with post-FNA changes ( 19 ). In terms of the pathogenic mechanism, needle injury causes direct interruption of the microvascular supply and venous thrombosis ( 7 8 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The novelty of ACR-TIRADS is the method of scoring both echogenic foci and calcifications, which are additive features given more weight than in other systems. Some authors have suggested modifying TIRADS [13,[20][21][22][23][24]. Park et al established a new system with 12 characteristics even though its application proved to be difficult, [13] and Kwak et al proposed a more practical classification system including only five US features [14].…”
Section: Overview Of Acr-tiradsmentioning
confidence: 99%